The ribosome as a missing link in the evolution of life. (21st February 2015) - Root-Bernstein, Meredith; Root-Bernstein, Robert
Abstract: Many steps in the evolution of cellular life are still mysterious. We suggest that the ribosome may represent one important missing link between compositional (or metabolism-first), RNA-world (or genes-first) and cellular (last universal common ancestor) approaches to the evolution of cells. We present evidence that the entire set of transfer RNAs for all twenty amino acids are encoded in both the 16S and 23S rRNAs of Escherichia coli K12; that nucleotide sequences that could encode key fragments of ribosomal proteins, polymerases, ligases, synthetases, and phosphatases are to be found in each of the six possible reading frames of the 16S and 23S rRNAs; and that every sequence of bases in rRNA has information encoding more than one of these functions in addition to acting as a structural component of the ribosome. Ribosomal RNA, in short, is not just a structural scaffold for proteins, but the vestigial remnant of a primordial genome that may have encoded a self-organizing, self-replicating, auto-catalytic intermediary between macromolecules and cellular life. Graphical abstract: Map Illustrating the Location of Transfer RNAs and Proteins in the Six Possible Reading Frames on the 23S, 16S and 5S Ribosomal RNAs of E. coli K12. Map suggests that rRNA once contained highly redundant and condensed genetic information encoding ribosome self-replication. "tRNA cut" means tRNAs can be excised from rRNAs; "tRNA transcribed" means tRNA production by transcribing the rRNA. Highlights: Hypothesize that ribosome was self-replicating intermediate between compositional or RNA-world and cellular life. rRNA contains genetic information encoding self-replication machinery: all 20 tRNAs and active sites of key ribosomal proteins. Statistical analyses demonstrate rRNA-encodings are very unlikely to have occurred by chance. Contradicts view of rRNA as purely structural suggesting instead that rRNA, mRNA and tRNA had common ribosomal ancestor. Suggest that DNA and cells evolved to protect and optimize pre-existing ribosome functions.